2006
DOI: 10.1063/1.2259815
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ion induced amorphicity on the diffusion of gold into silicon

Abstract: It is experimentally demonstrated that, after ion irradiating 60nm thick Au films on Si substrates with 230keV Ar+ ions, annealing conditions can be found leading to strong diffusional contrasts between bombarded and unbombarded areas. While Au readily diffuses into the bombarded part of the sample at 310°C, its diffusion is still completely blocked under identical conditions in the unbombarded parts. Clear evidence is provided that this diffusional contrast is due to bombardment induced amorphization of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Similar conclusion is available from the experiment of Ehrhard et. al, with a thick Au layer deposited on c-Si, a-Si and partially a-Si [6]. It was clearly shown that Au diffusion from top Au layer is more in a-Si than in c-Si and any intermediate crystalline layer (that is partially a-Si) will suppress the effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar conclusion is available from the experiment of Ehrhard et. al, with a thick Au layer deposited on c-Si, a-Si and partially a-Si [6]. It was clearly shown that Au diffusion from top Au layer is more in a-Si than in c-Si and any intermediate crystalline layer (that is partially a-Si) will suppress the effect.…”
Section: Resultsmentioning
confidence: 99%
“…Two mechanisms, namely the 'Frank-Turnbull' mechanism [2] and the 'kick-out' mechanism [3], have been used to explain the gold atoms' diffusion in crystalline silicon. In the case of amorphous silicon, the Au diffusion was explained in terms of direct diffusion, wherein the diffusing Au atoms were temporarily trapped by different kinds of vacancy-like effects [4,5]. In general, at high enough temperatures, the amorphous silicon (a-Si) recrystallizes and hence it would be difficult to study the diffusion of gold atoms in an a-Si system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used D(T) in the previous study [31]. Unknown parameters are ∆G and c(T) in Equation (5). From 480 to 600 K, we assume that ∆G in Equation 5is approximately expressed by a weak linear relation with temperature ( 0 1ΔG k k T = + ).…”
Section: Au Diffusion Process At the Early Stage Of Au Crystallizationmentioning
confidence: 99%
“…In metal silicides, metal-induced crystallization (MIC) [1]- [5] in thin films is well known to be a fundamental phenomenon relating to low eutectic point. Rather than viewing this phenomenon from a solid-phase reaction perspective, studies from the diffusion process view point are necessary due to the fact that electric screening weakens the covalent bonds of the amorphous Si (a-Si).…”
Section: Introductionmentioning
confidence: 99%